2001
DOI: 10.1073/pnas.251485198
|View full text |Cite
|
Sign up to set email alerts
|

Disruption ofPPT1orPPT2causes neuronal ceroid lipofuscinosis in knockout mice

Abstract: PPT1 and PPT2 encode two lysosomal thioesterases that catalyze the hydrolysis of long chain fatty acyl CoAs. In addition to this function, PPT1 (palmitoyl-protein thioesterase 1) hydrolyzes fatty acids from modified cysteine residues in proteins that are undergoing degradation in the lysosome. PPT1 deficiency in humans causes a neurodegenerative disorder, infantile neuronal ceroid lipofuscinosis (also known as infantile Batten disease). In the current work, we engineered disruptions in the PPT1 and PPT2 genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
303
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(320 citation statements)
references
References 33 publications
14
303
0
3
Order By: Relevance
“…Furthermore, the C57BL/6J strain is highly inbred resulting in less variability between individuals than in outbred strains such as CD1. In addition, mouse models for other neuronal ceroid lipofuscinoses, including CLN1, CLN6, and CLN8, have been established on the C57BL/6J strain background (Gupta et al, 2001;Lei et al, 2006;Ranta et al, 1999;Wheeler et al, 2002). Having all mouse NCL mutant models on the same strain background will facilitate phenotypic comparisons between the different mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the C57BL/6J strain is highly inbred resulting in less variability between individuals than in outbred strains such as CD1. In addition, mouse models for other neuronal ceroid lipofuscinoses, including CLN1, CLN6, and CLN8, have been established on the C57BL/6J strain background (Gupta et al, 2001;Lei et al, 2006;Ranta et al, 1999;Wheeler et al, 2002). Having all mouse NCL mutant models on the same strain background will facilitate phenotypic comparisons between the different mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Details concerning the construction of the PPT2 knockout mouse strain have been reported (10). All studies were performed by using PPT2 homozygous knockout (or WT control) mice on a mixed C57BL͞6J Ï« 129S6͞SvEvTac background.…”
Section: Methodsmentioning
confidence: 99%
“…We had previously observed that PPT2 knockout mice begin to develop a neurological phenotype by 10 mo of age (10). We have now carried out observations of a large cohort of these animals for 24 mo.…”
Section: Ppt2 In Brain Tissues and Neurological Phenotype In Knockoutmentioning
confidence: 98%
See 1 more Smart Citation
“…The palmitoyl protein thioesterases, PPT1 and PPT2, are involved in degradation of lipid-modified proteins in lysosomes, with each having distinct substrate specificity due to divergence in the substrate-binding regions (Camp and Hofmann, 1993;Camp et al, 1994;Soyombo and Hofmann, 1997). Loss of either PPT1 or PPT2 function results in the accumulation of lipidmodified material characteristic of lysosomal storage disorders such as infantile neuronal ceroid lipofuscinosis (INCL), and ultimately leads to cell death (Vesa et al, 1995;Gupta et al, 2001Gupta et al, , 2003Mitchison et al, 2004). APT1 and APT2 have been associated with dynamic palmitate cycling.…”
Section: Enzymes Implicated In Protein Depalmitoylationmentioning
confidence: 99%